Pengaruh Dimensi Green Economy Terhadap Zero Waste Behaviour Intention: Persepsi Masyarakat Kabupaten Wakatobi - Astil Harli Roslan; Ichsanuddin Akbar (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study uses a quantitative approach with Structural Equation Modeling (SEM) techniques to analyze the influence of the dimensions of the green economy on the intention of zero waste behavior in the community of Wakatobi Regency. The sample of the study consisted of 120 respondents who met certain criteria, namely individuals who have been involved in activities supporting the principles of the green economy and have the intention to adopt zero waste behavior. The results indicate that all three dimensions of the green economy have a positive and significant impact on the intention of zero waste behavior, with the economic dimension making the largest contribution, followed by the environmental and social dimensions. The theoretical implications of this study enhance the understanding of the relationship between green economy dimensions and pro-environmental behavior, while the practical implications can be used to design more effective policies and educational programs to increase community participation in zero waste behavior.